Strengthening Resource Management and Livestock Housing Systems to Maximize the Performance of BUMDes and Increase Village Revenue in Sukatani Village - Nugraha, Sukma; Adiansyah, Adi (Indonesian Journal of Community Empowerment (IJCE), 2025)
This Community Service Program (PKM) aims to enhance the capacity of the Sukatani Village-Owned Enterprise (BUMDes) managers in optimizing resource management and livestock housing management within the laying-hen farming business unit. The program was conducted through pretests, training sessions, discussions, and posttests involving village officials and BUMDes management members. The pretest results indicated a low level of understanding regarding resource management, poultry housing practices, and the role of BUMDes in improving village economic welfare. After the training, the posttest results showed a significant improvement in participants’ knowledge of operational management, cage sanitation, feed administration, and financial recording. The training proved effective in strengthening managerial competencies for more productive and sustainable BUMDes operations. Therefore, this PKM activity contributes to institutional capacity building and supports increased village income.